Beyond Britain : Stuart Hall and the postcolonializing of Anglophone cultural studies - Jensen, Lars (Rowman & Littlefield International, 2014)
"This book presents a history of the key ideas that have shaped the evolution of the shared spaces of inquiry in British Cultural Studies and Postcolonial Studies to analyse the continued significance and relevance of both disciplines beyond their British sites of origin"--Provided by publisher.